APRENDENDO ADMINISTRAÇÃO EM LABORATÓRIO: DESAFIOS E FRUSTRAÇÕES DE UMA EXPERIÊNCIA - Jorge Alberto dos Santos (Universidade Federal de Santa Catarina, 2012)
In this paper, we describe and reflect on the experience of the authors in setting up a new model of learning environment in management education in a Brazilian University. The learning environment would allow students to practise management skills in a setting called Management Practice Laboratory (MPL). The MPL environment was conceived as a physical and conceptual space where students could learn and practise the principles and techniques of working in organisations in their three levels: operational, tactical, and strategic. The foundations of our project come from the social constructivist perspective on learning, experiential learning literature, and research studies (HOUNSELL e ENTWISTLE, 2005) that call for a new epistemological ground in learning. Despite the challenges and frustrations, we conclude that once one shows courage to overcome the challenges and frustrations, there is room for innovation in the way one teaches and learns about management in Universities.